Mengukur Kinerja Keuangan Menggunakan Eva dan Rasio Aktivitas Pada Industri Farmasi Setelah Holding BUMN - Mokoginta, Rena Mustari (Forum Kerjasama Pendidikan Tinggi, 2023)
A company's financial performance, as based on value-added, can indicate its capacity to enhance the well-being of investors or shareholders. One of the notable accomplishments of firm management in financial management is the attainment of efficient financial performance through the optimal utilisation of company resources. This study aimed to measure the financial performance of the pharmaceutical industry after holding BUMN, utilising the EVA and activity ratios as measurement instruments. This study employed a descriptive analysis methodology to depict a symptom or scenario in its current state during this research without engaging in hypothesis testing. The study was conducted at PT Kimia Farma Tbk and PT Indonesia Farma Tbk, publicly listed on the Indonesia IDX. This data was selected using the documentation method and was analysed using EVA and Efficiency Ratio analysis instruments. The findings indicated that PT Indofarma Tbk financial performance could generate value added after holding BUMN in 2020 and 2021. On the one hand, PT Kimia Farma Tbk demonstrated the creation of value added after holding BUMN in 2021 and 2022. In addition, the findings indicated that the operational efficiency of PT Indofarma and PT Kimia Farma Tbk improved significantly after holding BUMN in 2021, as revealed by their enhanced financial performance.